Apparent diffusivity model for concrete containing supplementary cementitious materials - Riding, Kyle A.; Thomas, Michael D. A.; Folliard, Kevin J. (My University, 2014)
Concrete’s resistance to chloride diffusion is one of the primary factors governing the concrete structure service life and life-cycle costs. This paper presents a new model developed for estimating the apparent concrete diffusivity based on the mixture proportions, cementitious materials used, and concrete age. The model includes the effects of supplementary cementitious material types commonly found in other service life models such as fly ash, ground-granulated blast-furnace slag, and silica fume. Also included are ultra-fine fly ash and metakaolin, which were not available in previous service life models. For validation of the model, chloride profiles have been measured on concrete blocks exposed daily to seawater for 25 years at the Treat Island, ME concrete exposure site. Concrete mixtures tested as part of the validation dataset contained up to 80% ground-granulated blast-furnace slag, 25% fly ash, or 20% silica fume, and were compared against the predicted values and are presented in this paper.
Keywords: Diffusion; Long-term performance; Transport properties